Left-behind children and return migration in China - Sylvie Démurger; Hui Xu (IZA Journal of Migration, 2015)
This paper examines how left-behind children influence migration duration in China. We first present a simple illustrative model that incorporates economic and non-economic motives to migration duration. Using individual data from a survey carried out in Wuwei county (Anhui province) in 2008, we find that migrant parents of children in primary school tend to delay their return, a result we interpret as illustrating the need for migrant parents to accumulate money for their offspring's education. In contrast, parental time appears substitutable by coresiding grandparents who contribute to delay the parents' return, especially mothers, when they have children below the age of 12.
Keywords: J61; J13; C41; O53; 330; Return migration; Left-behind children; Discrete-time duration analysis; China